2020
DOI: 10.1097/ppo.0000000000000429
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy in the Management of Metastatic Hormone-Sensitive Prostate Cancer

Abstract: Systemic therapy has historically been the backbone of treatment for patients with metastatic disease. However, recent evidence suggests metastasis-directed therapy in those with oligometastatic disease (≤5 lesions) may improve progression-free and overall survival. Within prostate cancer–specific cohorts, metastasis-directed therapy also appears to delay the time to initiation of androgen deprivation therapy while also generally being associated with a mild toxicity profile and has thus garnered interest as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…We then attempted to stratify patients into modes of progression after therapy ( Fig. 1A , Table 3 ), 16 which appeared to fall into 3 classes. Class I included patients with long-term control (defined as no recurrence ≥18 months after therapy) of their disease after MDT and represented 40.9% of patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We then attempted to stratify patients into modes of progression after therapy ( Fig. 1A , Table 3 ), 16 which appeared to fall into 3 classes. Class I included patients with long-term control (defined as no recurrence ≥18 months after therapy) of their disease after MDT and represented 40.9% of patients.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, a better understanding of which subpopulations most benefit from MDT, and conversely which patients recur and their patterns and modes of progression, are needed to guide future treatment strategies. [16][17][18] Herein we report a retrospective multi-institutional study of 258 men treated to 474 total lesions and present patterns of recurrence and modes of progression after MDT in oligometastatic castrationsensitive prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Our primary and secondary end points were chosen with a phase 2 signal-finding goal 3 balanced against the potential harm of forestalling standard-ofcare systemic therapy. 4 Therefore, our primary end point was by design short and complemented by our secondary and exploratory end points, whereby which we demonstrated that the oligometastatic state may exist in CSPC, as shown by highly significant improvements not only in progression-free survival but, importantly, the development of new metastases by MDT alone. 1 With the short observation arm as a comparator, we were also able to definitively show in humans that SABR itself generates an adaptive systemic immune response.…”
Section: Metastasis-directed Therapy For Oligorecurrent Prostate Canc...mentioning
confidence: 95%
“…Patients with bone progressive disease detected by conventional imaging (as roughly half of the men enrolled in the trial) should receive systemic therapy. 4 Recent data have shown an even longer time to progression in the M1 recurrent setting by combining different systemic treatments. 5 Therefore, while we are accumulating compelling data supporting the earlier use of combined systemic approaches, we are reluctant in giving systemic treatment together with MDT.…”
Section: Metastasis-directed Therapy For Oligorecurrent Prostate Canc...mentioning
confidence: 99%
See 1 more Smart Citation